Reconstruction of alveolar bone defect with autogenous bone particles and osseointegrated implants: histologic analysis and 10 years monitoring - Carvalho, Paulo Sérgio Perri de; Carvalho, Mariliza Comar Astolphi de; Ponzoni, Daniela [UNESP] (Wolters Kluwer, 2015)
Maintaining the volume of the alveolar process after extraction can be achieved by immediate implant placement and guided bone regeneration, with or without the use of biomaterials. The authors present a case report with a 10 years follow-up, rehabilitation using osseointegrated implants in the extraction area and maintenance of the volume of the alveolar process with autogenous cortical bone shavings.
Keywords: Dental implants; Guided tissue regeneration; Particulate bone graft